The belt and road initiative in Asia, Africa, and Europe - Arase, David; Carvalho, Pedro Miguel Raposo de Medeiros, 1969- (Abingdon, Oxon ; New York, NY : Routledge, 2023)
"This book examines the progress and reception of China's Belt and Road Initiative (BRI) in key subregions of Asia, Africa and Europe. Through its exploration of the patchwork of distinctive sub regions of each continent, the book analyses how well the BRI accommodates sub regional variation as it attempts to integrate Asia, Africa, and Europe under Chinese auspices. Individual chapters focus on how developing subregions experience BRI relations with China, whilst others focus on how liberal powers seek to compete with China's BRI agenda. The contributions also gauge the impact of the Covid-19 pandemic on the BRI in regional settings and point to its future implications. Offering a panoramic view of the vast mosaic of Asian, African, and European sub regions targeted by the BRI, this book will be interest to scholars and students of International Relations and Global Political Economy as well as Chinese politics and those with an interest in the Belt and Road Initiative more broadly"--
Keywords: Yi dai yi lu (Initiative : China); Asian cooperation; Europe -- Foreign economic relations -- China; China -- Foreign economic relations -- Europe; Africa -- Foreign economic relations -- China; China -- Foreign economic relations -- Africa; Asia -- Foreign economic relations -- China; China -- Foreign economic relations -- Asia; POLITICAL SCIENCE / International Relations / General